Description of the Level of Satisfaction of Patients Visiting Clinic Pratama Santa Elisabeth Medan 2024 - Ginting, Amnita; Sigalingging, Vina YS; Monica, Monica (Mata Pena Madani, 2025)
Satisfaction refers to the assessment made by customers of the extent to which a product or service meets their needs and expectations. When the product or service cannot meet customer expectations or needs, this is considered a cause of dissatisfaction with the product or service. The level of patient satisfaction has several dimensional aspects consisting of reliability, assurance, tangibility, empathy and responsiveness. This study aims to determine description of the level of satisfaction of patients vsiting clinic pratama Santa Elisabeth Medan. The research is conducted at Santa Elisabeth Clinic Pratama Medan. The population in this study are 100 people. This type of research is descriptive with the data collection method used in the research, namely the accidental sampling technique. The results of the research show that the satisfaction of patients who visited Clinic Pratama Santa Elisabeth Medan is in Very Satisfied category of 34 respondents (34.0%), the Satisfied category of 51 respondents (51.0%), the Dissatisfied category of 10 respondents (10%), No 2 respondents (2%) are satisfied and 3 respondents (3%) are very dissatisfied. The conclusion of this research is that the better the communication provided by health workers with outpatients, the greater the outpatient satisfaction will be. The clinic needs to create a questionnaire on patient satisfaction levels and evaluate them regularly to find out the extent of satisfaction felt by patients after receiving services.